A fashion exhibition as cinematic experience. Issue 1 (1st April 2018) - Mida, Ingrid
Both the museum and cinema encourage the viewer to escape from the experience of the everyday and sequentially mobilize the gaze on a temporal itinerary that triggers personal affective responses. In this article, I will analyse the scenography of the exhibition Catwalk, a thematic display of historic dress at the Rijksmuseum in Amsterdam (20 February–22 May 2016). Designed by photographer Erwin Olaf, the exhibit made explicit connections to the catwalk even though many of the garments on display predate the origins of the catwalk or runway as a mode of presentation for fashion. The scenography negated the sensation of time and historicity and produced the affect of glamour, such that the Catwalk exhibition might be linked to Sophia Coppola's film Marie Antoinette (Coppola, 2006) in borrowing from the third-wave feminist aesthetic.